The Importance of Marketing for Higher Education Institutions ("Journal "U". Economy. Management. Finance.", 2021)
The article considers the modern essence of marketing for higher educational institutions. The aspect of effective interaction with the target audience through the translation of certain aspects of the university's activities is considered. The article also notes the development of competition in the market of educational services and the possibility of using it for established universities on the market.
Keywords: higher education institutions; marketing; educational services; applicants; target audience